2016
DOI: 10.1021/acs.jpca.6b06060
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the First Absorption Band of OCS Using Photofragment Excitation Spectroscopy

Abstract: Photofragment excitation spectra of carbonyl sulfide (OCS) have been recorded from 212−260 nm by state-selectively probing either electronically excited S( 1 D) or ground state S( 3 P) photolysis products via 2 + 1 resonance-enhanced multiphoton ionization. Probing the major S( 1 D) product results in a broad, unstructured action spectrum that reproduces the overall shape of the first absorption band. In contrast, spectra obtained probing S( 3 P) products display prominent resonances superimposed on a broad co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…REMPI spectra of the S photoproducts showed a broad, unstructured spectrum in the major S( 1 D 2 ) channel. 55 This suggests that the absorption spectrum and correspondingly the observed products are dominated by excitation to the repulsive 2 1 A (1 1 ∆) and 1 1 A (1 1 Σ − ) states, which lead to prompt dissociation, see also Figure 2. The repulsive nature of these two states along the dissociation coordinate was confirmed by earlier calculations 47 However, these calculations also indicated that these states have shallow local minima supporting bound vibrational states around bending angles of θ ≈ 40 • .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…REMPI spectra of the S photoproducts showed a broad, unstructured spectrum in the major S( 1 D 2 ) channel. 55 This suggests that the absorption spectrum and correspondingly the observed products are dominated by excitation to the repulsive 2 1 A (1 1 ∆) and 1 1 A (1 1 Σ − ) states, which lead to prompt dissociation, see also Figure 2. The repulsive nature of these two states along the dissociation coordinate was confirmed by earlier calculations 47 However, these calculations also indicated that these states have shallow local minima supporting bound vibrational states around bending angles of θ ≈ 40 • .…”
Section: Resultsmentioning
confidence: 91%
“…29 For graphical representations of the energies of all electronic states involved we refer the reader to, e. g., Figures 1 in refs. 49,55. Although the dissociation process responsible for the formation of rotationally excited CO(X 1 Σ + ) and S( 1 D 2 ) products is well understood and mainly attributed to prompt dissociation following the excitation of the 2 1 A (1 1 ∆) and 1 1 A (1 1 Σ − ) states, the mechanisms responsible for the formation of S( 3 P J ) fragments remains to be elucidated. Strong vibrational resonances were recently observed in the 2+1 resonance-enhanced multi-photon ionisation (REMPI) spectra of the S( 3 P J ) photoproducts recorded in a wavelength range from 212 nm to 260 nm, which were assigned to vibrational progressions in the C-S stretching following direct excitation to the 2 1 A (1 1 ∆) and triplet 2 3 A (1 3 Σ − ) metastable states.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the photolysis products orbital polarization effect of carbonyl sulfide has attracted enormous interest due to its important information of angular momentum [7][8][9][10][11]. In recent years, extensive experimental [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and theoretical [26][27][28][29] studies on the photodissociation dynamics of OCS in ultraviolet (UV) region have been reported.…”
Section: Introductionmentioning
confidence: 99%